The Relief of Unilateral Painful Thoracic Radiculopathy without Headache from Remote Spontaneous Spinal Cerebrospinal Fluid Leak - Byung-chul Son; Sang-woo Ha; Si-hoon Lee; Jin-gyu Choi (Pain Research and Management)
Spontaneous intracranial hypotension (SIH) caused by spontaneous spinal cerebrospinal fluid (CSF) leaks produces orthostatic headaches. Although upper arm pain or paresthesia is reportedly associated with SIH from spontaneous spinal CSF leak in the presence of orthostatic headache, low thoracic radicular pain due to spontaneous spinal CSF leak unassociated with postural headache is extremely rare. We report a 67-year-old female who presented with chronic, positional radicular right T11 pain. Computed tomography myelography showed a spontaneous lumbar spinal CSF leak at L2-3 and repeated lumbar epidural blood patches significantly alleviated chronic, positional, and lower thoracic radiculopathic pain. The authors speculate that a chronic spontaneous spinal CSF leak not severe enough to cause typical orthostatic headache or epidural CSF collection may cause local symptoms such as irritation of a remote nerve root. There might be considerable variabilities in the clinical features of SIH which can present a diagnostic challenge.